From Laboratory to Society: A Literature Analysis of Transforming Scientific Innovation into Real Technological Solutions - Setyo Lutfi Okta; Siti Hadiaty Yuningsih (International Journal of Research in Community Services, 2026)
The transformation of scientific innovation into real technological solutions remains a critical challenge in bridging the gap between research and societal impact. This study aims to analyze how innovation evolves from laboratory-based knowledge creation to widespread societal adoption through a systematic literature review. The research identifies key stages in the innovation transformation process, including knowledge creation, technology transfer, research commercialization, and innovation diffusion, and examines how these stages interact within a broader innovation ecosystem. The findings reveal that innovation transformation is a non-linear and dynamic process influenced by multiple factors, including institutional support, policy frameworks, and digital transformation. Technology transfer and knowledge exchange serve as essential mechanisms that connect scientific research with industrial application, while commercialization enables the translation of innovations into market-ready solutions. Furthermore, innovation diffusion determines the extent to which these solutions are adopted and generate economic and social value. The study also highlights the growing role of digital technologies, particularly artificial intelligence, in accelerating innovation processes and enhancing collaboration across sectors. However, the effectiveness of these technologies depends on organizational readiness and ecosystem alignment. Overall, the research proposes a holistic perspective on innovation transformation, emphasizing the importance of integrating technological, institutional, and societal dimensions to achieve sustainable and impactful outcomes.